Symptoms and patterns of symptom propagation in incipient ischemic stroke and migraine aura - Scutelnic, Adrian; Bracher, Jacqueline; Kreis, Lukas A.; Beyeler, Morin; Fischer, Urs; Arnold, Marcel; Mattle, Heinrich P.; Jung, Simon; Schankin, Christoph J. (Frontiers in Human Neuroscience, 2023)
Background and objectives: Taking a detailed history of symptoms is important for differentiating incipient ischemic stroke and migraine aura. The aim of our study is to describe in detail symptom type and temporal pattern of symptom evolution (i.e. symptom succession and the time lapse between symptoms) in patients with ischemic stroke and migraine with aura. Methods: Consecutive patients with ischemic stroke and migraine with aura were interviewed using a structured questionnaire. Stroke diagnosis was confirmed by imaging and migraine with aura was diagnosed according to the current criteria of the International Headache Society. Wake-up strokes and patients with severe cognitive deficits were excluded. Results: In stroke patients and migraine patients respectively, 50/78 (64%) vs. 123/326 (37%) had one, 18 (23%) vs. 127 (38%) had two, 5 (6%) vs. 69 (21%) had three, 2 (2%) vs. 4 (1%) had four, and 3 (3%) vs. 3 (1%) had five visual symptoms. In respect of sensory symptoms, 76/145 (52.4%) vs. 116/175 (66%) reported paresthesia and 92/145 (63.4%) vs. 132 (75%) numbness. Looking at the beginning, visual symptoms were the first symptom more often in migraine aura than in ischemic stroke (72.1% vs 18.8%, P < 0.001). Sensory (29% vs 13.9%, P = 0.001) and motor symptoms (20.5% vs 1.4%, P <0.001) were the first symptom more frequently in ischemic stroke. Of patients with consecutive symptoms, 39 of 211 (18%) compared to 34 of 117 (29%) (P = 0.02) reported at least two simultaneous symptoms. A time lapse between symptoms of <1 minute (18.6% vs 6.3%, P < 0.001) and >360 minutes (15.8% vs 0%, ꭓ2 = 39.61, P < 0.001) was more frequent in stroke whereas a time lapse between 5 and 60 minutes was more frequent in migraine aura (41.1% vs 68.7%, P < 0.001). Conclusions: There is a significant overlap in the clinical presentation of stroke and migraine aura. In particular, a substantial proportion of patients in one group had symptoms that are traditionally attributed to the other group. This study highlights the similarities between symptoms of ischemic stroke and migraine aura and challenges our reasoning in daily clinical practice.